#TITLE_ALTERNATIVE# - SUNARTO (NIM 12804009); Pembimbing : Dra. Atika Lubis, M.S., FAISAL
Development of the region of Malang city can not be separated from the change of land use from open space area to paved area, especially for urban areas. Flood and puddle of rainwater is a problem that arose due to changes in land use is not set properly. Urban area has an infiltration capacity of rainwater that is less than open space area. When the urban become larger will be more rainwater that was changed to surface runoff. When the surface runoff amount is larger than the region's ability to stream the water then there will be puddle of rainwater and floods. Rainfall, topography and land use are factors that greatly determine the surface runoff flow pattern. SCS method (Soil Conservation Service) is used to determine changes in surface runoff amount as the effects of changes in land use. Rainfall areas of the use obtained from the calculation isohyets method use data from 6 meteorological stations (Karangploso, Brawijaya, Sumberasin, AR Saleh, Selorejo and Karangkates). Water balance calculation using the FJ Mock method and the evapotranspiration calculated with the Penman equation. Topography obtained from the sample height of 520 sample area, which then interpolated to obtain the 3D condition. Topography of the area then determines the surface runoff direction and potential flow velocity potential at Malang area. For the period 2001-2008 growing of urban area in the Malang City is 20.92% and has increased the amount of surface runoff by 8.6%. Zoning Regulation is based on the surface runoff flow pattern, rainfall areas, and Rencana Tata Ruang dan Wilayah (RTRW) Kota Malang 2008-2028. Area south of Malang with rainfall annual average of 2123.04 mm/year is an area that is planned as a green open space area or agricultural area. Mainly focused on Buring Hill which the region have the high potential flow velocity on 9-13.5% steepness. Improvement of drainage capacity and built of check dam is some alternative that can be applied to overcome the flood and puddle of rainwater problem. Bango, Brantas and Sukun sub catchments area a priority because it is in the area is relatively flat so that the flow of surface runoff will be more easily obstructed.